People and audit process attributes of audit quality: evidence from Malaysia / Noor Adwa Sulaiman, Suhaily Shahimi and Ranjit Kaur Nashtar Singh - Sulaiman, Noor Adwa; Shahimi, Suhaily; Nashtar Singh, Ranjit Kaur (Accounting Research Institute (ARI), UiTM Shah Alam, 2019)
This study seeks to add to understanding of the concept and attributes of audit quality from the perspective of those responsible for delivery audit services, the auditors, as a key constituent group in the auditing system. The study surveyed two groups of external auditors (group 1- audit partners and managerial level and, group 2 - senior auditors and junior auditors), as a basis to compare their perceptions on important of auditors and audit process attributes in achieving audit quality in practice. The study was conducted in the form of a survey, with data being gathered via questionnaire. Returned surveys from external auditors yielded a 37% response rate. Overall, top 5 highest rated attributes of audit quality reported to be most important in determining audit quality are: compliance with the International Standard Quality Control (ISCQ) 1, obtaining credible and sufficient audit evidence, technical expertise of audit team, audit work meeting the audit firms’ quality standards, and competency of the audit team. Further analysis shows that the two groups of respondents have differential views on attributes of audit quality in practice. Group 1 perceived attributes of audit quality are related to auditor’s assessment of risk and internal quality review procedures within the audit firm. In comparison, group 2 perceived auditors’ competency and compliance with relevant standards as indicators of audit quality. This study suggests differences in underlying view about attributes audit quality in practice by the two groups of auditors. Public accounting firms might be interested to understand such underlying differences so that efforts in improving audit quality in practice would be focusing on the key attributes that perceived to be important on delivery high-quality audit services. This study is significant by extending the literature on audit quality and also provides useful input to public accounting firms in improving audit quality in practice.